2002
DOI: 10.1002/dev.10083
|View full text |Cite
|
Sign up to set email alerts
|

Sexual interactions of maturing male guinea pigs with their mothers, sisters, and unfamiliar adult females in the home cage

Abstract: During observations in the home cage in the light and dark on days 5, 15, 25, 35, and 45, male guinea pigs mounted and exhibited anogenital investigation of the mother, though appropriately directed mounting occurred infrequently and was not shown by all males. Mothers nipped and kicked advancing males. No mounting of a female sibling was observed. When behavioral interactions of approximately 35-day-old males with the mother or an unfamiliar adult female were compared during 1-hr tests in the home cage, males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We suggested that the increase in hippocampal MR expression, combined with the increase in plasma testosterone, which is known to inhibit HPA function in the rat (Viau et al 1999), resulted in reduced HPA function. Male guinea pigs are sexually mature by approximately 8 weeks of age (Hennessy et al 2003). Castration of male guinea pigs, rats and hamsters has been shown to increase ACTH and cortisol production as well as CRH and arginine vasopressin (AVP), while androgen replacement reversed this effect (El Hani et al 1980; Viau & Meaney, 1991; Handa et al 1994; McCormick et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We suggested that the increase in hippocampal MR expression, combined with the increase in plasma testosterone, which is known to inhibit HPA function in the rat (Viau et al 1999), resulted in reduced HPA function. Male guinea pigs are sexually mature by approximately 8 weeks of age (Hennessy et al 2003). Castration of male guinea pigs, rats and hamsters has been shown to increase ACTH and cortisol production as well as CRH and arginine vasopressin (AVP), while androgen replacement reversed this effect (El Hani et al 1980; Viau & Meaney, 1991; Handa et al 1994; McCormick et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…& Pitstick, 2003). Similarly, the females can exhibit adultlike social behavior and sometimes reach sexual maturity by this age (Young, 1969).…”
mentioning
confidence: 99%
“…Although offspring maintained with the mother several weeks after weaning appear to treat her much as do preweaning pups, sexual motivation is emerging at this age (i.e., ∼5–7 weeks). The males readily direct courtship and sexual behavior toward unfamiliar adult females (Hennessy, Reed, Wilson, & Pitstick, 2003). Similarly, the females can exhibit adultlike social behavior and sometimes reach sexual maturity by this age (Young, 1969).…”
mentioning
confidence: 99%